2022
DOI: 10.21203/rs.3.rs-1274068/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comparative Study of Calcified Epithelioma of Malherbe And Epidermoid Cyst With Ultrasound

Abstract: Objective: To explore the ultrasonic(US)features of calcified epithelioma Malherbe (CEM) and epidermoid cyst(EC) in differential diagnosis and improve the accuracy of US diagnosis of CEM.Materials and Methods: We retrospectively analyzed 309 subjects, who underwent US examination before operation and pathological diagnosis for CEM or EC post-operation. The subjects were categorized into the training and validation sets according to different inspection times. The US and clinical features of CEM were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 15 publications
(21 reference statements)
2
4
1
Order By: Relevance
“…Magnetic resonance imaging (MRI) has high resolution in soft tissues, and it is often used for the diagnosis of skin focal lesions, such as the identification of dermatofibrosarcoma protuberans, but it is hard to make a reliable diagnosis of pilomatricoma, 17,18 Typical epidermoid cysts with unique features such as the fistula sign or submarine sign and onion sign can be confidently diagnosed using HFUS examination 19 . However, typical epidermoid cysts with uncommon features may be mistaken for other lesions 20,21 . In our study, there were five epidermoid cysts with the fistula sign or submarine sign and one epidermoid cyst with an ambiguous onion sign, and these features did not appear in pilomatricomas and dermatofibrosarcomas protuberans.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Magnetic resonance imaging (MRI) has high resolution in soft tissues, and it is often used for the diagnosis of skin focal lesions, such as the identification of dermatofibrosarcoma protuberans, but it is hard to make a reliable diagnosis of pilomatricoma, 17,18 Typical epidermoid cysts with unique features such as the fistula sign or submarine sign and onion sign can be confidently diagnosed using HFUS examination 19 . However, typical epidermoid cysts with uncommon features may be mistaken for other lesions 20,21 . In our study, there were five epidermoid cysts with the fistula sign or submarine sign and one epidermoid cyst with an ambiguous onion sign, and these features did not appear in pilomatricomas and dermatofibrosarcomas protuberans.…”
Section: Discussionsupporting
confidence: 93%
“…Of the hypoechoic rim, we used the criterion from the Type 2 in the study by Pelizzari et al 5 Only five pilomatricomas were found to have a hypoechoic rim (7.9%, 5/63), while there were nine epidermoid cysts with a hypoechoic rim (11.8%, 9/76) in our study, as shown in Figures 4 and 7. Therefore, the presence of a hypoechoic rim is not a unique diagnostic factor for pilomatricoma, which differs from the findings of Choo et al 6 and Wei et al 21 The reason for this discrepancy may be the variation in inter-reader agreement for identifying a hypoechoic rim.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations